INTERPERSONAL COMMUNICATION IN REALIZING RELIGIOUS MODERATION IN TRENGGALEK DISTRICT - Nanda Elma Fitriani; Galih Akbar Prabowo (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2023)
In order to achieve religious moderation, the inhabitants of Trenggalek Regency engaged in interpersonal communication, which is the focus of this study. Data gathering for this study involved both observation and interviews, following a qualitative research methodology. The findings demonstrated that interpersonal communication was successful in educating the residents of Trenggalek Regency about religious moderation there. With this, the neighborhood, which has never experienced interfaith conflict, may bring about harmony among its residents. Religious moderation is crucial in society. Every human being aspires to the fulfillment of holy peace. Importantly, Trenggalek practice of religion comports with the established social order and presents no risk of conflict. One of the benefits of interpersonal communication is the recognition of religious harmony.